2020
DOI: 10.3390/cancers12082033
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profile of Lymphovascular Invasion, a Known Risk Factor of Pancreatic Ductal Adenocarcinoma Metastasis

Abstract: Lymphovascular invasion (LVI) is an aggressive pathologic feature and considered a risk factor for distant metastasis. We hypothesized that pancreatic ductal adenocarcinomas (PDACs) with LVI are associated with shorter survival, as well as aggressive cancer biology and lymphangiogenesis in transcriptomic analysis. Utilizing the cancer genome atlas (TCGA)-PDAC cohort, we found that positive LVI was significantly associated with positive perineural invasion (PNI) (p = 0.023), and higher American Joint Committee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…Yamazaki et al reported that epithelial–mesenchymal transition (EMT) activity in PC is a promising prognostic biomarker. Our group reported that high activity of the G2M checkpoint pathway [ 5 ] and lympho-vascular invasion [ 6 ] is associated with worse survival. In contrast, the abundance of mature blood vessels [ 7 ] and fibroblasts in PC [ 8 ] is associated with better survival.…”
Section: Introductionmentioning
confidence: 99%
“…Yamazaki et al reported that epithelial–mesenchymal transition (EMT) activity in PC is a promising prognostic biomarker. Our group reported that high activity of the G2M checkpoint pathway [ 5 ] and lympho-vascular invasion [ 6 ] is associated with worse survival. In contrast, the abundance of mature blood vessels [ 7 ] and fibroblasts in PC [ 8 ] is associated with better survival.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of the 17 studies with a total of 7427 patients are summarized in Table 1 [ 7 12 , 14 , 15 , 17 , 20 24 , 28 30 ]. All articles were retrospective and observational studies, 4 of which were from China, 6 were from the USA, 3 were from Japan, and the others were from Italy, South Korea, and France.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 17 reports of retrospective studies that described the incidence of MVI in PDAC cases ( Figure 2 ) [ 7 12 , 14 , 15 , 17 , 20 24 , 28 30 ]. Thesestudies evaluated 7427 cases of PDAC, including 4029 cases with MVI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations